Federal tax transfers and demographic transition: Balancing equity and efficiency - Lekha Chakraborty; Yadawendra Singh (Levy Economics Institute of Bard College, 2024)
Against the backdrop of demographic transition in India, the study highlights the necessity of integrating the elderly population as a critical factor in formula-based intergovernmental fiscal transfers. The demographic transition, characterized by an increasing elderly population, imposes unique fiscal challenges on states, necessitating a revision of transfer formulas to ensure equitable and efficient resource distribution. The paper employs a historical analysis of fiscal devolution criteria, and analyzes the impact of incorporating the elderly population into the devolution formula on the share of states in the total tax transfer to states. The findings indicate that integrating the elderly population into the tax devolution formula can significantly alter the distribution of resources among states, with states benefiting more while having a relatively larger elderly population. The study recommends considering demographic changes by incorporating the elderly to working age population ratio as a criterion used by the Sixteenth Finance Commission to promote a more equitable and efficient allocation of resources.
Keywords: H77; J11; J16; 330; fiscal transfer; tax devolution; demographic transition; gender inequality